Morphology and polymorphic phase changes of calcium carbonate micro/nanocrystals using fruit extracts - Ankamwar, Balaprasad (Journal of Nanoscience and Nanotechnology, 2011)
This study reveals the morphology and polymorphic phase changes of calcium carbonate crystals into a mixture of calcite and aragonite micro/nanocrystals of interesting morphology at room temperature by a simple reaction with fruit extracts of Tamarindus indica and Emblica officinalis respectively by mixing CaCO(3) solutions with their corresponding extracts. The control experiments were carried out to establish the plausible role of tartaric acid from Tamarindus indica and ascorbic acid from Emblica officinalis in this regard. The quantitative determination of CaCO(3) phases was done based on the use of intensities obtained from corresponding XRD spectrum. The molar %. of aragonite was found to be more in case of TA and AA rather than TI and EO respectively, however the calcite was observed to be the predominant phase in all four reactions. Interestingly, the TI changes the rhombohedral morphology of calcite to elongated rods, whereas EO induces a great polymorphic phase change.
Keywords: Aragonite; Calcite; Emblica officinalis; Morphology Changes; Polymorphic Changes; Tamarindus indica

Continuous precipitation of calcium carbonate using sonochemical reactor - Shirsath, S. R.; Sonawane, S. H.; Saini, D. R.; Pandit, A. B. (Ultrasonics Sonochemistry, 2015)
The continuous production of calcium carbonate (CaCO3) by precipitation method at room temperature was carried out in a stirred reactor under ultrasonic environment and was compared with the conventional stirring method. The effect of various operating parameters such as Ca(OH)(2) slurry concentration, CO2 flow rate and Ca(OH)(2) slurry flow rate on the particle size of CaCO3 was investigated. The calcium carbonate particles were characterized by Fourier transform infrared (FTIR), wide angle X-ray diffraction (WXRD) and particle size. The morphology was studied by using scanning electron microscopic (SEM) images. The particle size obtained in the presence of ultrasonic environment was found to be smaller as compared to conventional stirring method. The particle size is found to be reduced with an increase in the concentrations of Ca(OH)(2) and increased with increasing CO2 flow rate for both the methods. The slurry flow rate had a major effect on the particle size and the particle size decreased with increased slurry flow rate. Only calcite phase of CaCO3 was predominantly present as confirmed by the characterization techniques for both the preparation methods. In most of the cases rhombohedral calcite particles were observed. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Calcite; Crystal growth; Morphology; Nucleation; Particle size; Ultrasound